2015
DOI: 10.1016/j.biombioe.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional landscapes: Site characterization and field-scale design to incorporate biomass production into an agricultural system

Abstract: Sustainability GHG emissionsNitrate leachate Marginal landsNutrient recovery a b s t r a c t Current and future demand for food, feed, fiber, and energy require novel approaches to land management, which demands that multifunctional landscapes are created to integrate various ecosystem functions into a sustainable land use. We developed an approach to design such landscapes at a field scale to minimize concerns of land use change, water quality, and greenhouse gas emissions associated with production of food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 55 publications
0
49
0
Order By: Relevance
“…Although studies have tried to justify the costs of conservation practices by monetizing the benefits obtained through enhanced water quality and ecological services, the economic benefits for in situ recovery of leached nutrients are rarely considered. When integrated with biomass production, the intercepted nutrients may be reused by energy crops, like switchgrass, to generate economic returns . In recent years, integrated landscape management strategies, such as using riparian buffers with perennial grasses or woody biomass crops have been gaining increased attention because they can take advantage of both the effectiveness of conservation practices in reducing nutrient loss and the economic potential of cellulosic biomass as bioenergy feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have tried to justify the costs of conservation practices by monetizing the benefits obtained through enhanced water quality and ecological services, the economic benefits for in situ recovery of leached nutrients are rarely considered. When integrated with biomass production, the intercepted nutrients may be reused by energy crops, like switchgrass, to generate economic returns . In recent years, integrated landscape management strategies, such as using riparian buffers with perennial grasses or woody biomass crops have been gaining increased attention because they can take advantage of both the effectiveness of conservation practices in reducing nutrient loss and the economic potential of cellulosic biomass as bioenergy feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…For example, within a single corn field, Ssegane et al . () showed that areas of low crop yield coincided with high NO 3 ‐N leaching due to low soil fertility related to high water infiltration. This and other research has highlighted the importance of within‐field variability to management practices that balance economic and environmental performance (Delgado & Berry, ; Kyveryga et al ., ; Muth, ).…”
Section: Introductionmentioning
confidence: 99%
“…Landscape placement of bioenergy crops predicates the allocation of specific crops to landscape positions to better match their growth habit and environmental performance to land characteristics. In most cases, these matches imply subfield‐scale partitioning of land based on soil properties, elevation, shallow groundwater flow, and other characteristics . Subfield‐scale crop allocation can be important in cases where overall field economics are negatively impacted by areas of low productivity in otherwise productive fields .…”
Section: Introductionmentioning
confidence: 99%
“…In these underproductive lands, bioenergy crops may provide opportunities to reduce economic losses caused by yields not meeting the cost of production . In other cases, targeting perennial bioenergy crops to subfield areas prone to cause environmental damage may prove beneficial in meeting priority conservation targets …”
Section: Introductionmentioning
confidence: 99%